Effects of Classroom-Based Resistance Training With and Without Cognitive Training on Adolescents’ Cognitive Function, On-task Behavior, and Muscular Fitness - Robinson, Katie J.; Lubans, David R.; Mavilidi, Myrto F.; Hillman, Charles H.; Benzing, Valentin; Valkenborghs, Sarah R.; Barker, Daniel; Riley, Nicholas (Frontiers in Psychology, 2022)
Aim: Participation in classroom physical activity breaks may improve children’s cognition, but few studies have involved adolescents. The primary aim of this study was to examine the effects of classroom-based resistance training with and without cognitive training on adolescents’ cognitive function. Methods: Participants were 97 secondary school students (45.4% female, mean age 15.78 ± 0.44). Four year 10 classes from one school were included in this four-arm cluster randomized controlled trial. Classes were randomly assigned to the following groups: sedentary control with no cognitive training, sedentary with cognitive training, resistance training without cognitive training, and resistance training with cognitive training. Sessions varied in levels of both cognitive demand and resistance training (i.e., high vs low) and were administered three times per week for four weeks (12 sessions). Inhibition, cognitive flexibility, episodic memory, on-task behavior, and muscular fitness were assessed at baseline and post-test. Linear mixed models were used to examine changes within and between groups. Results: In comparison to the control group, episodic memory improved significantly in the resistance training without cognitive training group (-9.87 units, 95% CI: -17.71 to -2.03, p = .014, d = 0.72). There were no group-by-time effects for inhibition or cognitive flexibility. Classroom activity breaks both with and without cognitive demand improved participants’ on-task behavior in comparison to the control and sedentary group. The resistance training programs did not lead to improvements in muscular fitness. Conclusion: Participation in body weight resistance training without cognitive training led to selective improvements in episodic memory. No training effects were found for inhibition or cognitive flexibility. A longer study period may be necessary to induce improvements in muscular fitness and associated changes in inhibition and cognitive flexibility.